A Defect in Interleukin-10 Leads to Enhanced Malarial Disease in Plasmodium chabaudi chabaudi Infection in Mice - Li, Ching (American Society for Microbiology, 1999)
Infection of interleukin-10 (IL-10)-nonexpressing (IL-10(−/−)) mice with Plasmodium chabaudi chabaudi (AS) leads to exacerbated pathology in female mice and death in a proportion of them. Hypoglycemia, hypothermia, and loss in body weight were significantly greater in female IL-10(−/−) mice than in male knockout mice and all wild-type (WT) mice during the acute phase of infection. At this time, both female and male IL-10(−/−) mice produced more gamma interferon (IFN-γ), tumor necrosis factor alpha (TNF-α), and IL-12p40 mRNA than their respective WT counterparts. Inactivation of IFN-γ in IL-10(−/−) mice by the injection of anti-IFN-γ antibodies or by the generation of IL-10(−/−) IFN-γ receptor(−/−) double-knockout mice resulted in reduced mortality but did not affect body weight, temperature, or blood glucose levels. The data suggest that IFN-γ-independent pathways may be responsible for these pathological features of P. chabaudi malaria and may be due to direct stimulation of TNF-α by the parasite. Since male and female knockout mice both produce more inflammatory cytokines than their WT counterparts, it is likely that the mortality seen in females is due to the nature or magnitude of the response to these cytokines rather than the amount of IFN-γ or TNF-α produced.